Serum neutrophil gelatinase-associated lipocalin as a potential biomarker for cognitive decline in spinal cord injury - Zhang, Qinghao; Li, Ziteng; Xie, Liangyu; Cao, Shengnan; Cui, Zhonghao; Shi, Bin; Chen, Yuanzhen (Frontiers in Neurology, 2023)
Objective Neutrophil gelatinase-associated lipoprotein (NGAL), a protein encoded by the lipocalcin-2 (LCN2) gene, has been reported to be involved in multiple processes of innate immunity, but its relationship with spinal cord injury (SCI) remains unclear. This study set out to determine whether NGAL played a role in the development of cognitive impairment following SCI. Methods At the Neck-Shoulder and Lumbocrural Pain Hospital, a total of 100 SCI patients and 72 controls were enrolled in the study through recruitment. Through questionnaires, baseline data on the participants' age, gender, education level, lifestyle choices (drinking and smoking) and underlying illnesses (hypertension, diabetes, coronary heart disease, and hyperlipidemia) were gathered. The individuals' cognitive performance was evaluated using the Montreal Cognitive Scale (MoCA), and their serum NGAL levels were discovered using ELISA. Results The investigation included 72 controls and 100 SCI patients. The baseline data did not differ substantially between the two groups, however the SCI group's serum NGAL level was higher than the control group's (p < 0.05), and this elevated level was adversely connected with the MoCA score (p < 0.05). According to the results of the ROC analysis, NGAL had a sensitivity of 58.24% and a specificity of 86.72% for predicting cognitive impairment following SCI. Conclusions The changes in serum NGAL level could serve as a biomarker for cognitive impairment in SCI patients, and this holds true even after taking in account several confounding variables.